Sociedades en conflicto: Movimientos sociales y movimientos armados en América Latina - González Arana, Roberto (CLACSO, 2016)
Latin America creates a paradox in its geography that has fed the various social science power plants, in pursuit of an explanatory matrix: being a continent rich in the most diverse resources on the one hand and having the most unequal and unjust societies on the planet, on the one hand. the other. The history of the continent puts in black on white how difficult and expensive (in human lives, especially), that it has been, and still is, to reverse this situation. There we believe that the title of this collective work finds full justification. This is a sharing between the working group of the Latin American Council of Social Sciences (CLACSO) «Social Movements and Revolutionary Movements in Central America and the Caribbean» and the Institute of Higher Social and Cultural Studies of Latin America and the Caribbean of the University North of Colombia (UNINORTE).